Leadership in Action In Focus - Leadership Characteristics - Nine Keys to Good Leadership - Campbell, David (Center for Creative Leadership, 2002)
Effective leadership is crucial to the success of any enterprise, and understanding and emulating the features of a good leader can improve one's chances of success in a leadership role.
Title from content provider
Keywords: Leadership